Online Implementation of Project-Based Learning (PJBL) on Students' Capacity for Creative Thinking - Samsi Samsi; Disman Disman; Eeng Ahman; A Sobandi; Hari Mulyadi (CV. Tripe Konsultan, 2026)
Creative thinking is the process of coming up with original, adaptable, and visually appealing solutions to problems. Creative thinking is the continuous process of thinking about and creating creative things in order to achieve objectives. Students find the project-based learning approach and the learning process to be interesting experiences. Student learning experiences with the upcoming project serve as the focus of the instructional materials. Students learn more and feel more motivated to complete assigned projects when they are given real-world experience in the learning process. Students learn more and feel more motivated to complete the assigned project when they are given real-world experience in the learning process. Creative thinking is the process of coming up with original, adaptable, and visually appealing solutions to problems. This study looked into how collaboration between groups improved collaborative learning groups' performance on project-based learning tasks and the co-construction of knowledge. The findings of two case studies, one on between-group mentoring and one on between-group project review, revealed that both strategies were viewed favorably by the students and had a positive impact on all students' project performance, particularly in the less effective groups, as well as the knowledge revealed through their online dialogue. The findings shed some light on how students in higher education engage in computer-supported collaborative learning.